2022
DOI: 10.3389/fpls.2022.1033805
|View full text |Cite
|
Sign up to set email alerts
|

Two vacuolar invertase inhibitors PpINHa and PpINH3 display opposite effects on fruit sugar accumulation in peach

Abstract: Soluble sugars are an important determinant of fruit taste, but their accumulation mechanisms remain elusive. In this study, we report two vacuolar invertase inhibitor genes involved in sugar accumulation in peach, PpINHa and PpINH3. Transient overexpression of PpINH3 in peach fruits resulted in an increase in sugar content, while the opposite trend was detected for PpINHa. Unexpectedly, PpINH3 and PpINHa both had no physical interaction with vacuolar invertase (VIN). Moreover, the PpVIN genes had no or extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Prupe.1G530300.1 and Prupe.1G034400.1 were discovered to function as potential positive regulators of sugar accumulation [59]. We carried out functional analyses using their transient overexpression in peach fruits to validate this discovery.…”
Section: Transient Overexpression Of Prupe1g5303001 and Prupe1g034400...mentioning
confidence: 97%
See 1 more Smart Citation
“…Prupe.1G530300.1 and Prupe.1G034400.1 were discovered to function as potential positive regulators of sugar accumulation [59]. We carried out functional analyses using their transient overexpression in peach fruits to validate this discovery.…”
Section: Transient Overexpression Of Prupe1g5303001 and Prupe1g034400...mentioning
confidence: 97%
“…We carried out functional analyses using their transient overexpression in peach fruits to validate this discovery. Gene expression levels and sugar content in the fleshy tissue surrounding the infiltration sites were assessed five Prupe.1G530300.1 and Prupe.1G034400.1 were discovered to function as potential positive regulators of sugar accumulation [59]. We carried out functional analyses using their transient overexpression in peach fruits to validate this discovery.…”
Section: Transient Overexpression Of Prupe1g5303001 and Prupe1g034400...mentioning
confidence: 99%
“…Vimolmangkang et al investigated the mechanisms regulating sucrose accumulation in peach fruit and found that there were two sucrose-cleaving enzyme genes (SUS4 and NINV8), one sucrose resynthesis gene (SPS3) and three sugar transporter genes (SUT2, SUT4 and TMT2) involved in sucrose metabolism and transport [16]. Moreover, sugar content in peach fruit is increased by the transient overexpression of the vacuolar invertase inhibitor gene PpINH3 associated with sugar accumulation, whereas PpINHa causes the opposite trend [20]. These results indicate that differences in the expression of genes and pathways related to sugar metabolism may lead to differences in the sugar content of fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Peach (Prunus persica (L.)) is extensively cultivated in China, ranging from 23 • to 45 • N. China is the leading global producer of peach fruit [1], which is renowned for its nutritional value and distinctive flavor. However, peach fruit is susceptible to chilling injury (CI) during low-temperature storage, which compromises its flavor and quality, thereby failing to satisfy consumer preferences [2].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in sugar concentrations in leaves and roots can significantly affect photosynthesis and respiratory metabolism, respectively [4]. Environmental stresses, such as temperature stress, drought, and salt, can limit plant growth and development and cause significant crop losses [1,5]. Among the various stresses, low temperature stress holds significant importance [6].…”
Section: Introductionmentioning
confidence: 99%